TIME-OF- USE ELECTRICITY RATE IMPACT IN THE ECONOMIC ANALYSIS ON OF SOLAR DOMESTIC HOT-WATER SYSTEMS - Abreu, Samuel L.; Starke, Allan R.; Fernandes, Rubipiara C.; Cardemil , José Miguel (Anais Congresso Brasileiro de Energia Solar - CBENS, 2016)
Brazilian demand curve for the residential sector has most of the times a typical shape with a pronounced peak from 18-22 hours. A time-of-use rate was recently introduced to incentive consumers to manage their demand in order to avoid electricity consumption during on-peak hours. Solar Domestic Hot-Water Systems can be a useful tool to reduce the energy consumption and on-peak power demand but represents additional investment costs, so depending on the electricity costs, they can be an economically feasible option. The present work shows an optimization procedure to define the sizing of the Solar Domestic Hot Water System for a study case that considers an average hourly electricity consumption for water heating of 60 dwellings. It presents a multi-objective optimization analysis considering the conflicting objectives of the consumers that want a lower monthly expenditure and the utility company that wants to smooth the demand curve. Results shows that considering the actual regulation, solar heating systems are economically feasible for both rates with a slightly advantage to the time-of-use rate. Reduction in the on-peak electricity consumption is always achieved.